2014
DOI: 10.14740/cr333e
|View full text |Cite
|
Sign up to set email alerts
|

Improving ECG Competence in Medical Trainees in a UK District General Hospital

Abstract: Background: Competency in electrocardiogram (ECG) interpretation is central to undergraduate and postgraduate clinical training. Studies have demonstrated ECGs are interpreted sub-optimally. Our study compares the effectiveness of two learning strategies to improve competence and confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 6 publications
0
59
0
Order By: Relevance
“…The ECG is an indispensable diagnostic modality in cardiac disease 1 2. Although knowledge of, and skills in ECG analysis and interpretation, hereafter referred to as ECG competence, are desired learning outcomes of undergraduate and postgraduate medical training programmes, there is ongoing concern that graduating medical trainees lack adequate ECG competence 3–12. Many reasons account for this observation.…”
Section: Introductionmentioning
confidence: 99%
“…The ECG is an indispensable diagnostic modality in cardiac disease 1 2. Although knowledge of, and skills in ECG analysis and interpretation, hereafter referred to as ECG competence, are desired learning outcomes of undergraduate and postgraduate medical training programmes, there is ongoing concern that graduating medical trainees lack adequate ECG competence 3–12. Many reasons account for this observation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the lack of ECG competence, undergraduate and postgraduate students also lack con dence in ECG analysis and interpretation, which improves with training. 14 In this study we observed that students exposed to blended learning were more con dent in ECG analysis and interpretation at the end of their Clinical Clerkship. This con dence matched their competence in basic ECG analysis and the interpretation of abnormal rhythms and waveforms.…”
Section: Discussionmentioning
confidence: 62%
“…A larger significant benefit was seen in those were in the teaching program. 26 On the contrary, Kopeć et al showed that competency in interpretation of the ECG is gained mainly by self-learning, whereas attendance at regular ECG classes failed to improve the skill of ECG reading. 19 Our results show a moderately level of ECG misreading among sixth-year medical students and interns at Taif University.…”
Section: Discussionmentioning
confidence: 99%